Pengembangan usaha akomodasi bagi wisata minat khusus: Studi kasus Desa Ngawas, Kabupaten Pasuruan Provinsi Jawa Timur - Sugito . (HOSPITALITI DAN PARIWISATA, 2018)
The land of PT. Hide Way Resort area 1.5 ha located in Ngawas village, Pasuruan district, the Province of East Java as at the moment is empty land and was planted apple, Eugenia, red pepper, carrot and pumpkin. It is located almost at the same position with Mount Bromo. This land will be used for accommodation/ 10 villas and 1 meeting room. We have to drive and reach this location and can see the apple and vegetable garden on mountain also very nice scenery we can see during passing this location. Also, we can see the natural village condition and warmest welcome from the people around the village. We can see very nice view after reaching the place by mountain view and hill view in cold temperature. Land and hill view on the area make more convenience to stay here. This kind of location can attract the tourist especially specific tourist who always searching the specific destination since it is not many kind of destination like this. The main concept is staying in natural village with traditional villa style and look like the traditional house in the past including the furniture inside and how to cook the food by burning wood. This kind of situation also completed with daily people around the village activities, traditional art show, transportation to Mount Bromo, golf and other activities. The marketing activities will be used the relationship of the owner with his channels abroad, community of specific tourism, you tube, social media and online travel agent. This opportunity is good to be developed in the future since many inquiry for this kind of specific tourism, increase the economy level of the people around and create more working opportunity.